System Analysis and Design of Armament Integrated Management System - Appavuraj, R.; Gupta, Pranab Kumar Das; Ghosh, Pranab; Samal, P.B.; Saha, Anjan (Defence Science Journal, 2014)
Proof and trial activity in a dynamic test range is a complex, sensitive, and herculean activity. It is a system comprising critical functions that accept various armament inputs and produces proof results as output, processing various critical data and sensitive activities in between. Automation of the existing system is a step for reliable, secure, smooth operation and easy maintainability of the system that makes it synchronized with the latest development of range technology. Understanding the flow of data through these functions requires extensive study to realize different inter-linked activities involved with the functions of this system. This paper presents the flow of activities in the automation of dynamic test range of Proof & Experimental Establishment through context level diagram, process flow diagram, data flow diagram, and entity-relationship diagram. Realization of armament integrated management system will be through resilient and high bandwidth network backbone which is a part of this paper. Cloud computing is the latest development in the information technology. This paper also analyses the appropriate model of cloud computing for porting the system in the cloud. Science Journal, Vol. 64, No. 6, November 2014, pp.524-529, DOI:http://dx.doi.org/10.14429/dsj.64.8113